Relationship Between Cognitive Assessment and Balance Measures in Adolescents Referred for Vestibular Physical Therapy After Concussion. Issue 1 (January 2016) - Alsalaheen, Bara A.; Whitney, Susan L.; Marchetti, Gregory F.; Furman, Joseph M.; Kontos, Anthony P.; Collins, Michael W.; Sparto, Patrick J.
Abstract : Objective: To examine the relationship between cognitive and balance performance in adolescents with concussion. Design: Retrospective case series. Setting: Tertiary. Patients: Sixty patients. Interventions: Correlation analyses were performed to describe the relationship between symptoms, cognitive measure, and balance measure at the time of initiation of vestibular physical therapy. Main Outcome Measures: Cognitive performance was assessed using the Immediate Post-concussion Assessment and Cognitive Testing (ImPACT). The dizziness and balance function measures included dizziness severity rating, Activities-specific Balance Confidence scale (ABC), Dizziness Handicap Inventory (DHI), Functional Gait Assessment, gait speed, Timed "UP and GO, " Five Times Sit to Stand, and Sensory Organization Test (SOT). To account for multiple comparisons, the False Discovery Rate method was used. Results: Performance measures of balance were significantly correlated with cognitive measures. Greater total symptom scores were related to greater impairment in the ABC and DHI (r = 0.35-0.39, P ⩽ 0.008) and worse performance in condition 2 of the SOT (r = −0.48, P = 0.004). Among the ImPACT composite scores, lower memory scores were correlated with impaired balance performance measures (r = 0.37-0.59, P ⩽ 0.012). Lower visual memory was also correlated with worse ABC scores. Conclusions: The significant relationships reported between the cognitive performance scores and balance measures may reflect that similar levels of functioning exist across domains in individuals with protracted recovery who receive vestibular physical therapy. Clinical Relevance: The weak-to-moderate relationships warrant the continuous use of multiple domains of assessment. A better understanding to the relationships between the domains of functioning after concussion may improve the overall management approach for adolescents with concussion.